1986
DOI: 10.1210/endo-119-4-1467
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptides GLP-1 and GLP-2, Predicted Products of the Glucagon Gene, Are Secreted Separately from Pig Small Intestine but Not Pancreas*

Abstract: We developed specific antibodies and RIAs for glucagon-like peptides 1 and 2 (GLP-1 and GLP-2), two predicted products of the glucagon gene, and studied the occurrence, nature, and secretion of immunoreactive GLP-1 and GLP-2 in pig pancreas and small intestine. Immunoreactive GLP-1 and GLP-2 were identified in glucagon-producing cells of the pancreatic islets, and in glicentin-producing cells of the small intestine. Immunoreactive GLP-1 and 2 in intestinal extracts corresponded in molecular size to peptides sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
233
5
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 445 publications
(254 citation statements)
references
References 18 publications
(23 reference statements)
13
233
5
3
Order By: Relevance
“…Similar L-cells are found in the large intestine [7,8] and preproglucagon gene expression has been demonstrated in the colon [1,6]. These observations, together with the demonstration of GLP-l-immunoreactive staining co-localising with glicentin in the ileum [6,9,11], colon [12] and rectum [10], and the presence of GLP-1 immunoreactivity in tissue extracts of large and small intestine [6] led to the assumption that processing of proglucagon in these tissues is similar, even though the molecular nature of the GLP-1 immunoreactivity was not identified. In a later study, Mojsov et al [18] showed that the majority of GLP-1 immunoreactivity in the rat large and small intestine co-eluted on HPLC with synthetic GLP-I (7-36)amide, although a small proportion eluted in the position of non-amidated, glycine-extended GLP-1 (7-37).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar L-cells are found in the large intestine [7,8] and preproglucagon gene expression has been demonstrated in the colon [1,6]. These observations, together with the demonstration of GLP-l-immunoreactive staining co-localising with glicentin in the ileum [6,9,11], colon [12] and rectum [10], and the presence of GLP-1 immunoreactivity in tissue extracts of large and small intestine [6] led to the assumption that processing of proglucagon in these tissues is similar, even though the molecular nature of the GLP-1 immunoreactivity was not identified. In a later study, Mojsov et al [18] showed that the majority of GLP-1 immunoreactivity in the rat large and small intestine co-eluted on HPLC with synthetic GLP-I (7-36)amide, although a small proportion eluted in the position of non-amidated, glycine-extended GLP-1 (7-37).…”
Section: Discussionsupporting
confidence: 52%
“…Many L-cells are also found in the large intestine, where the preproglucagon gene is also known to be expressed [1,6] in enteroglucagon producing cells [7,8]. GLP-1 and GLP-2 immunostaining is co-localised with glicentin/enteroglucagon staining in open-type endocrine cells in the ileum of all mammals studied so far [6,[9][10][11], and GLP-1 immunostaining has been shown in both the colon [12] and the rectum [10]. However, although the presence of a GLP-1-immunoreactive moiety has been demonstrated in the large intestine, it is not known how proglucagon is processed in the large intestine, or whether true biologically active GLP-I (7-36)amide is formed.…”
Section: Introductionmentioning
confidence: 99%
“…This gene is expressed not only in the pancreatic alpha-cells, but also in the L-cells of the intestinal mucosa, one of the most abundant endocrine cells of the gut [32]. Here the primary translation product, proglucagon, is cleaved, not to produce glucagon as in the islets, but to release from its C-terminal part the two glucagon-like peptides GLP-1 and GLP-2 [33], both showing about 50% sequence homology with glucagon. The N-terminal part of the precursor, which includes the glucagon-sequence, is secreted as a single, rather large, peptide, designated glicentin (formerly gut glucagon or GLI) which, most likely, is biologically inactive.…”
Section: Glucagon-like Peptide-1 (Glp-1)mentioning
confidence: 99%
“…These sequences were flanked by pairs of basic amino acids, predicted posttranslational processing sites, suggesting that the two peptides might be cleaved out of the precursor to be released to the blood stream. This turned out to be the case for proglucagon produced in the intestinal L-cells, whereas proglucagon produced in the pancreatic alpha cells was cleaved into glucagon and a large C-terminal fragment, the socalled major proglucagon fragment [20,21].…”
Section: Discovery Of Glucagon-like Peptide-1mentioning
confidence: 99%